(untitled) (Sains Humanika, 2014)
Malaysia aims to achieve a high-income nation status by 2020. Thus, highly skills and knowledge workforce are essential to support this vision. In line with Malaysia’s economic transformation, Technical Vocational Education and Training (TVET) especially Malaysia Skills Certification System (MSCS) has been regarded as one of the main routes in providing the skilled workforce in order to meet the employment. Although job opportunities are wide open for TVET graduates in various fields through economic transformation, but the study showed that only half of the MSCS graduates choose to work in the technical and skills sectors. Thus, the requirement of 1.3 million jobs in the TVET become constraints. Thus, this paper will provide an overview of career choice among MSCS students and to propose a model of career choice to solve the issue. A systematic review methods which includes 332 refferences has been used to provide an exhaustive summary of literature and subsequently generate a significant framework to examine the relationship between the person, environment, and the adaptability towards student career choice. Adaptability has also been proposed as a mediator in this study. The substantial framework consider the combination of previous theories and the current TVETâ€™s environment in anticipating MSCS studentâ€™s career choice.